Membayangkan Indonesia dari Novel-Novel Antaretnis dan Antaragama Periode 1920-an Hingga 1970-an - Dwi Rahariyoso (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2015)
Husband research outlines the issue of inter-ethnic and inter-religious marriages are hearts novel Indonesia the 1920’s period until 1970's. Novel category grouping by genre what are hearts novel-novel that had the capacity hearts discuss the theme of interethnic and inter-religious marriages. The hearts raised through a new genre, patterns and The narrative structure can be observed carefully. Category interethnic and interreligious new hearts 1920’s period until 1970's indicated that awareness about multiculturalism, pluralism, and nationality AS an idea essentials personal identity of the Indonesian nation. The full diversity of the national spirit already a central issues in developed posted author that period through the storys of romance (romance) youth hearts modern Indonesian novel.